2022
DOI: 10.3390/su14159000
|View full text |Cite
|
Sign up to set email alerts
|

Research Topic Specialization of Universities in Information Science and Library Science and Its Impact on Inter-University Collaboration

Abstract: Universities significantly empower the development of science and technology, and inter-university research collaborations have been one of the major approaches. Considering each university has its expertise regarding research topics in a given discipline, the present paper examines the specialization of university research and its impact on inter-university collaborations. Based on a keyword network constructed via research articles in Information Science and Library Science, 10 research topics are identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…For instance, Hong et al [34], using data from Italian researchers in the field of materials science, found a positive correlation between the number of patents granted to researchers and their research output in terms of academic papers. Similarly, Hou et al [35], using data from Japanese researchers, discovered a positive linear relationship between the number of patents and publications in journals with low impact factors. Additionally, Hu et al [36], analyzing patent data in the nanotechnology field from three European countries, found that researchers with patents had more publications and higher citation rates than those without patents.…”
Section: Cross-level Mediating Effect Of Researchers' Technological C...mentioning
confidence: 86%
“…For instance, Hong et al [34], using data from Italian researchers in the field of materials science, found a positive correlation between the number of patents granted to researchers and their research output in terms of academic papers. Similarly, Hou et al [35], using data from Japanese researchers, discovered a positive linear relationship between the number of patents and publications in journals with low impact factors. Additionally, Hu et al [36], analyzing patent data in the nanotechnology field from three European countries, found that researchers with patents had more publications and higher citation rates than those without patents.…”
Section: Cross-level Mediating Effect Of Researchers' Technological C...mentioning
confidence: 86%